On the Non-Equilibrium Behavior of Fuel-Rich Hydrocarbon/Air Combustion Within Perfectly Stirred Reactors. Issue 4 (3rd April 2017) - Celis, Cesar; Figueira da Silva, Luis Fernando
ABSTRACT: The observed origins of non-equilibrium behavior, even for relatively large residence times in perfectly stirred reactors (PSRs) burning fuel-rich mixtures, are addressed. These PSR deviations from chemical equilibrium are characterized by using PSR-based results of CO/O2 reacting mixtures. Accordingly, the origins of the PSR non-equilibrium behavior are elucidated by (i) analyzing the relevance of the reaction steps involved in the CO/O2 kinetic mechanism, (ii) deriving and assessing analytical expressions reproducing the PSR results, and (iii) examining asymptotic limit solutions emphasizing a possible cause of the non-equilibrium behavior observed. The main results highlight that the PSR non-equilibrium behavior is controlled by a competition between (i) the rate of progress variable backward component of the CO + O + M ⇌ CO2 + M reaction and (ii) the ratio between the reactor inlet O2 molar concentration and the reactor residence time. Thus, even when the reactor is operating in a region of temperature invariance (plateau), where chemical equilibrium conditions could be presumed, there are some chemical species, such as O2 and O, whose steady state does not correspond to that of chemical equilibrium. It is concluded then that particular attention should be paid when analyzing PSR results obtained at relatively high mixture equivalence ratios, which may not correspond to equilibrium, in situations where it could be presumed to happen. A brief discussion on the extent of such non-equilibrium phenomena is performed as well as using more complex syngas/O2 mixtures.